THE EFFECT OF SERVICE QUALITY AND EMPLOYEE DISCIPLINE OF COMMUNITY SATISFACTION IN THE LAND OFFICE OF EAST LAMPUNG REGENCY - Edy Kurniawan (Universitas Muhammadiyah Metro, 2020)
This study aims to determine empirically the Effect of Service Quality and Employee Work Discipline on Community Satisfaction in the Land Office of East Lampung Regency. The method used is quantitative, data collection using interviews, documentation and questionnaires. The data analysis technique is using multiple linear regression formula. The results showed that: Hypothesis 1, supported / accepted, which means that there is an influence of service quality on community satisfaction at the East Lampung District Land Office. Hypothesis 2, supported / accepted, which means that there is an effect of employee work discipline on community satisfaction at the East Lampung District Land Office. Hypothesis 3, supported / accepted, which means there is an Influence of Service Quality and Employee Work Discipline on Community Satisfaction in the Land Office of East Lampung Regency. The magnitude of the effect of the Influence of Service Quality and Employee Work Discipline on Community Satisfaction in the Land Office of East Lampung Regency is 32%.